Evaluating a Taxonomy for Mobility Requirements by a Controlled Experiment. (3rd November 2011) - Gopalakrishnan, Sundar; Karpati, Peter; Sindre, Guttorm
Abstract : Requirements taxonomies have been found useful in software requirements elicitation and specification, both for educational purposes and in practical usage, for instance, as checklists to ensure that important categories of requirements are not forgotten, and for guidance on how to write various types of requirements. While mobile information systems are becoming increasingly important, traditional requirements taxonomies do not have any category for mobility requirements. This paper reports on a controlled experiment where two groups of students both got the same excerpts of the well-known Volere requirements taxonomy, but for one treatment group the tutorial material was also extended with additional material on mobility requirements as a requirements category in its own right. Using the provided taxonomy material for guidance, the students were asked to write requirements for a system presented in a natural language case description; afterwards their output was analyzed to score the number and quality of requirements found by each student. The main finding was that the students using the extended taxonomy also found more requirements, but there was no significant difference in the quality of requirements between the two groups.